ITINERÁRIOS DE EVA PERÓN: FÁBULA, BIOGRAFIA, FICÇÃO - Pereira, André Luis Mitidieri (Revista Literatura em Debate, 2013)
No presente artigo, identifico a biografia contida em um dos três níveis narrativos de Santa Evita, obra literária do escritor e jornalista argentino Tomás Eloy Martínez. Confronto a fábula biográfica que integra esse romance, focado em Eva Perón, com biografias e narrativas historiográficas também centradas nessa personalidade histórica. O modelo actancial de Greimas, longe de uma aplicação meramente estruturalista, comprova que o nível biográfico da narrativa sob análise propicia discutir as relações entre história e ficção suscitadas pelo texto. EVA PERÓN’S PATHWAYS: FABLE, BIOGRAPHY, FICTION The present article aims at identifying a biography which conforms into one of the three narrative levels of Santa Evita, literary work produced by the Argentinean writer and journalist Tomás Eloy Martínez. The kind of biographical fable contained in this novel focusing Eva Perón is checked with other biographies and historiographical narratives also centered in that historical personality, better known as Evita. Far from being a merely structuralist approach, Greimas actantial model proves that the narrative’s biographic level enables one to discuss the relationship between history and fiction in Martinez´ text.